1992
DOI: 10.1111/j.1651-2227.1992.tb12164.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of cow's milk protein intolerance in steroid‐resistant nephrotic syndrome

Abstract: The role of cow's milk protein intolerance in steroid-resistant nephrotic syndrome was evaluated in 17 children. Cow's milk was excluded from the diet for at least 14 days without changing previously ineffective prednisone dosage. Six patients with minimal change or mesangial proliferation went into remission 3 to 8 days after elimination of cow's milk. After a period of 2-3 weeks of remission, cow's milk challenge was positive in three patients. After one year on a cow's milk-free diet, two of six patients be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…and nephrotic syndrome, and milk elimination significantly improves symptoms of both diseases, including steroid-resistant idiopathic nephrotic syndrome (50)(51)(52). It is interesting to speculate that these findings might unify the pathogeneses of nephrotic syndrome and atopy through cellular and molecular responses to food allergens and IL-13.…”
Section: Discussionmentioning
confidence: 99%
“…and nephrotic syndrome, and milk elimination significantly improves symptoms of both diseases, including steroid-resistant idiopathic nephrotic syndrome (50)(51)(52). It is interesting to speculate that these findings might unify the pathogeneses of nephrotic syndrome and atopy through cellular and molecular responses to food allergens and IL-13.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, patients may not have had true MCD because some patients had steroid resistance42,43 or multiple relapses38 and were maintained during the trial at the same previous dose of steroids found to be not effective. Some reports also included patients younger than 1 year, making MCD less likely, and some included kidney biopsy specimens that showed a pathological state other than MCD.…”
Section: Food Allergens and Nephrotic Syndromementioning
confidence: 99%
“…There is an emphasis on maintaining appropriate growth and electrolyte homeostasis during infancy and childhood, as well as preventing early onset cardiovascular disease. The goal of the chapter is to expand Length of time between initiating diet therapy and remission of NS Sandberg et al [76] >3 years of age Cow's milk (10) Specific avoidance Remission occurred within 3 days to 1 month Laurent et al [77] Possible gluten/wheat (4) Rasoulpour et al [80] Egg, chicken, and cow's milk (1) Gluten, pork, and cow's milk (1) Beef, pork, and egg (1) Sieniawska et al [78] <3 years of age the awareness of the importance of nutrition in improving CKD outcomes throughout the life course journey. The topics covered in the chapter are in accordance with current NIH research goals [84].…”
Section: Resultsmentioning
confidence: 99%
“…In the early 1990s, Sieniawska et al evaluated the effects of a dairy-free diet in 17 patients ages 1-15 years with steroid-resistant nephrotic syndrome [78]. Six of the 17 subjects responded to the milk proteinfree diet with remission of nephrotic syndrome.…”
Section: Hypoallergenic Diet As a Treatment For Idiopathic Nephrotic mentioning
confidence: 98%